The Importance of Providing Incentives and Motivation in Improving Employee Performance - Sihabudin (International Journal of Science and Society, 2019)
This study aims to examine the effect of incentives and motivation on employee performance at PT. Hurip Utama Cikampek. This research was conducted using descriptive and verification methods, namely collecting, presenting, analyzing, and testing hypotheses, and making conclusions. Samples were collected using the Incidental Random Sampling method with a total sample of 128 respondents from a population of 281 people. Data analysis techniques used are scale range analysis techniques and SPSS version 22 path analysis. The results of this study prove that there is an influence between incentives and motivation on employee performance at PT. Hurip Utama Cikampek both partially and simultaneously.